MRZ-99030 – A novel modulator of Aβ aggregation: II – Reversal of Aβ oligomer-induced deficits in long-term potentiation (LTP) and cognitive performance in rats and mice. (May 2015) - Rammes, Gerhard; Gravius, Andreas; Ruitenberg, Maarten; Wegener, Nico; Chambon, Caroline; Sroka-Saidi, Kamila; Jeggo, Ross; Staniaszek, Lydia; Spanswick, Dave; O'Hare, Eugene; Palmer, Philip; Kim, Eun-Mee; et al.
Abstract: β-amyloid1-42 (Aβ1-42 ) is a major endogenous pathogen underlying the aetiology of Alzheimer's disease (AD). Recent evidence indicates that soluble Aβ oligomers, rather than plaques, are the major cause of synaptic dysfunction and neurodegeneration. Small molecules that suppress Aβ aggregation, reduce oligomer stability or promote off-pathway non-toxic oligomerization represent a promising alternative strategy for neuroprotection in AD. MRZ-99030 was recently identified as a dipeptide that modulates Aβ1-42 aggregation by triggering a non-amyloidogenic aggregation pathway, thereby reducing the amount of intermediate toxic soluble oligomeric Aβ species. The present study evaluated the relevance of these promising results with MRZ-99030 under pathophysiological conditions i.e. against the synaptotoxic effects of Aβ oligomers on hippocampal long term potentiation (LTP) and two different memory tasks. Aβ1-42 interferes with the glutamatergic system and with neuronal Ca 2+ signalling and abolishes the induction of LTP. Here we demonstrate that MRZ-99030 (100–500 nM) at a 10:1 stoichiometric excess to Aβ clearly reversed the synaptotoxic effects of Aβ1-42 oligomers on CA1-LTP in murine hippocampal slices. Co-application of MRZ-99030 also prevented the two-fold increase in resting Ca 2+ levels in pyramidal neuron dendrites and spines triggered by Aβ1-42 oligomers. In anaesthetized rats, pre-administration of MRZ-99030 (50 mg/kg s.c.) protected against deficits in hippocampal LTP following i.c.v. injection of oligomeric Aβ1-42 . Furthermore, similar treatment significantly ameliorated cognitive deficits in an object recognition task and under an alternating lever cyclic ratio schedule after the i.c.v. application of Aβ1-42 and 7PA2 conditioned medium, respectively. Altogether, these results demonstrate the potential therapeutic benefit of MRZ-99030 in AD. Highlights: β-amyloid (Aβ) is a major endogenous pathogen in Alzheimer's disease (AD). Soluble Aβ oligomers are the major cause of synaptoxicity/neurodegeneration in AD. MRZ-99030 promotes off-pathway, non-toxic oligomerization of Aβ. MRZ-99030 reversed the synaptotoxic effects of Aβ oligomers in vitro and in vivo . MRZ-99030 ameliorated cognitive deficits in NOR and ALCR tasks.